Varicella-zoster-virus vaccination of immunosuppressed children with inflammatory bowel disease or autoimmune hepatitis: A prospective observational study. Issue 50 (25th November 2020) - Seitel, Teresa; Cagol, Luana; Prelog, Martina; Frivolt, Klara; Krahl, Andreas; Trenkel, Stefan; Speth, Fabian; Mayer, Benjamin; Almanzar, Giovanni; Koletzko, Sibylle; Debatin, Klaus-Michael; Mertens, Thomas; et al.
Highlights: Data on safety and immunogenicity of live vaccination in immunosuppressed patients are scarce. Physicians need a simple risk assessment to decide on vaccination of immunosuppressed children. Varicella zoster vaccination was well tolerated and immunogenic in patients with IBD or AIH. A clinical- and laboratory-based approach may ensure safety and immunity of the VZV vaccine strain. Abstract: Background and aims: Children with inflammatory bowel disease (IBD) and autoimmune hepatitis (AIH) receiving immunosuppressive treatment are at risk for severe varicella zoster virus (VZV)-induced disease. This study evaluated vaccination of susceptible patients with stable disease and documented immunoreactivity without interruption of their current immunosuppression (IS). Methods: This prospective multicentre observational study used a prevaccination checklist to select patients with low-intensity and high-intensity IS for VZV vaccination. Tolerability and safety after immunization were assessed by questionnaire. The immune response was measured by the VZV-IgG concentration, relative avidity index (RAI), and specific lymphocyte proliferative response. Results: A total of 29 VZV vaccinations were performed in 17 seronegative patients aged 3–16 years (IBD n = 15, AIH n = 2). Eight patients received high-intensity immunosuppression, another six low-intensity immunosuppression, and three patients interrupted IS before VZV vaccination. All 29 vaccinations were well tolerated; only minor side effects such as fever and abdominal pain, were reported in two patients. One patient experienced a flare of Crohn's disease the day after vaccination. The VZV-IgG-concentration increased significantly (p = 0.018) after vaccination, and a specific lymphocyte response towards VZV in vitro was detected in all tested patients which correlated with the RAI (r = 0.489; p = 0.078). Conclusions: VZV vaccination was well tolerated, safe and immunogenic in children receiving ongoing IS due to IBD and AIH. Ensuring immunoreactivity by clinical and laboratory parameters, rather than the type and dosage of IS, is a reasonable approach to decide on live-attenuated virus vaccinations in immunosuppressed children (German clinical trials DRKS00016357).